ChemInform Abstract: Periconiasin G, a New Cytochalasan with Unprecedented 7/6/5 Tricyclic Ring System from the Endophytic Fungus Periconia sp. Issue 23 (19th May 2016) - Zhang, Dewu; Tao, Xiaoyu; Liu, Jimei; Chen, Ridao; Zhang, Min; Li, Li; Fang, Xiaomei; Yu, Li‐Yan; Dai, Jungui
Abstract: New cytochalasans, periconiasin G (I) and periconiasin H (II) are isolated from Periconia sp.